2019
DOI: 10.1093/sleep/zsz192
|View full text |Cite
|
Sign up to set email alerts
|

Economic aspects of insomnia medication treatment among Medicare beneficiaries

Abstract: Study Objectives To examine economic aspects of insomnia and insomnia medication treatment among a nationally representative sample of older adult Medicare beneficiaries. Methods Using a random 5% sample of Medicare administrative data (2006–2013), insomnia was defined using International Classification of Disease, Version 9, Clinical Modification diagnostic codes. Treatment was operationalized as one or more prescription fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Patients included in this study were on average 82 years old, which is similar to other claims-based studies of newly-diagnosed AD [20][21][22]. However, a higher percentage were female (67% versus 53%-63%) [21][22][23][24], which may reflect the higher prevalence of insomnia among women, as found in other studies [8,25]. In addition to being more common, some research suggests that in women insomnia presents in more complex ways with more symptoms [26] and that the adverse effects of insomnia and sleep loss are more severe among women compared to men with regards to cardiovascular health [27,28], risk of diabetes [28], and psychological affect, functioning, and quality of life [28,29].…”
Section: Discussionsupporting
confidence: 80%
“…Patients included in this study were on average 82 years old, which is similar to other claims-based studies of newly-diagnosed AD [20][21][22]. However, a higher percentage were female (67% versus 53%-63%) [21][22][23][24], which may reflect the higher prevalence of insomnia among women, as found in other studies [8,25]. In addition to being more common, some research suggests that in women insomnia presents in more complex ways with more symptoms [26] and that the adverse effects of insomnia and sleep loss are more severe among women compared to men with regards to cardiovascular health [27,28], risk of diabetes [28], and psychological affect, functioning, and quality of life [28,29].…”
Section: Discussionsupporting
confidence: 80%
“…Inpatient costs, followed by outpatient costs, were the primary drivers of total costs both pre- and post-insomnia diagnosis, in both treated and untreated cohorts. Surprisingly, this previous Medicare analysis showed no significant difference in total costs between the treated and untreated cohorts during the 12 months prior and 12 months post-insomnia diagnosis [ 42 ]. In another study, relative to non-sleep disordered controls, patients with untreated insomnia demonstrated $63,607 (95% CI: $60,532, $66,685) higher all-cause healthcare utilization and costs in the 11 months prior to insomnia diagnosis or matched index date, with inpatient care accounting for most of the healthcare use and costs (2019 USD) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, slope changes suggested that prescription costs continued to decrease afterward. While prior claims database analyses assessing real-world economic outcomes in patients with insomnia exist [23][24][25][26], none have yet Fig. 4 Trend over time for monthly total healthcare costs and medical costs (2018 US dollars) before and after initiation of suvorexant for a prevalent insomnia cohort and b incident insomnia cohort.…”
Section: Discussionmentioning
confidence: 99%